PEMETAAN GENETIK VIRUS RABIES PADA ANJING SEBAGAI DASAR PENETAPAN PENGENDALIAN PENYAKIT (Genetic Mapping of Rabies Virus in Dogs as a Basis for Disease Control) - Muharam Saepulloh; R. M. Abdul Adji (Universitas Syiah Kuala, 2016)
The purpose of this study was to determine the genetic characteristics of rabies virus based on phylogenetic relationship among rabies virus in various regions in Indonesia. The amino acid sequence of the nucleoprotein gene of rabies virus isolate from Banten (RV/Banten-01/dog/2007), Makasar (RV/MKS-26/dog/2010), Bukit Tinggi (RV/BKT-52/dog/2009 and RV/BKT-58/dog/2009), Medan (RV/Medan-27/dog/2007) and Bali (RV/Bali-1/dog/2009; RV/Bali-2/dog/2009; RV/Bali-3/dog/2009), Indonesia was determined. These isolates showed a high degree of homology among Indonesian isolates which reached 100%. Meanwhile, the level of homology between rabies virus isolates from cats rabies virus isolates from dogs reached 97%. Results of phylogenetic analysis using the amino acid sequences of the N genes showed that all of Indonesian rabies virus isolates were closely related to rabies viruses from China than those from Thailand, Laos, Burma, and Vietnam which geografically closer to Indonesia. Data obtained from the phylogenetic analysis is expected to trace the source of rabies spread and the possibility to create a vaccines which more suitable with rabies virus that spreads in Indonesia. Based on the phylogenetic relationship analysis using the amino acid sequence of the rabies virus N protein gene showed that all of rabies virus isolated from Indonesian regions share a high homology with others ranging from 97-100%.Key words: sequencing, rabies, nucleoprotein gene (N), homology